2021
DOI: 10.1038/s41467-021-23038-7
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-induced electrochemistry at an electrically asymmetric carbon Janus particle

Abstract: Chemical doping through heteroatom substitution is often used to control the Fermi level of semiconductor materials. Doping also occurs when surface adsorbed molecules modify the Fermi level of low dimensional materials such as carbon nanotubes. A gradient in dopant concentration, and hence the chemical potential, across such a material generates usable electrical current. This opens up the possibility of creating asymmetric catalytic particles capable of generating voltage from a surrounding solvent that impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In addition to energy generation, this enduringly maintained electrical potential could be potentially useful for many other applications, especially in the field of sensing and information technology, such as multi‐responsive sensors, memristor and electrochemical transformations. [ 25,38 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to energy generation, this enduringly maintained electrical potential could be potentially useful for many other applications, especially in the field of sensing and information technology, such as multi‐responsive sensors, memristor and electrochemical transformations. [ 25,38 ]…”
Section: Resultsmentioning
confidence: 99%
“…In addition to energy generation, this enduringly maintained electrical potential could be potentially useful for many other applications, especially in the field of sensing and information technology, such as multi-responsive sensors, memristor and electrochemical transformations. [25,38] In essence, the absorbed water content determines the gradient, and hence the behavior of the AHS. It is then inferred that losing water due to an external thermal stimulus could lead to output loss, but it has been demonstrated that the functionality of the AHS is restorable after water re-absorption.…”
Section: Asymmetry-induced Electricity Generation Of Ahsmentioning
confidence: 99%
“…Oxidizing alcohols using hypochlorite anions has been previously demonstrated using TEMPO or nickel (II) salts as a catalyst, suggesting that the HClO produced at the H x WO 3 electrode may also carry out these oxidation reactions. To test the efficiency of the chloride oxidation coupled alcohol oxidation process, we conducted CPC experiments. Figure a shows the reaction progress from quantitative 1 H NMR spectroscopy over the 8 1/2 hour CPC experiment.…”
Section: Resultsmentioning
confidence: 99%
“…The voltage may be supplied by either harvested (e.g., a solar cell or a photodiode) or stored energy (e.g., a zinc-air battery), both of which have been miniaturized for sub-100 μm-scale applications. [5,39,79,80] While the basic fixed resistors are commonly found in memristor circuits as secondary parasitic electrical elements, for instance to account for the wiring resistance, [81] they are essential in our architecture to create the one-at-a-time switching sequence that encodes time (Figure 1D): Assuming an initial condition where all memristors are ON (M n ¼ R ON , ∀n), any current would preferentially pass through M 1 closest to the energy source. Consequently, M 1 is selectively switched OFF, or at least largely, before the current bypasses the now highly resistive M 1 and starts switching OFF M 2 .…”
Section: On-board Time Awarenessmentioning
confidence: 99%